2022
DOI: 10.1029/2022gc010568
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Evolution of the Swell and Magmatic Fluxes Along the Louisville Hotspot Chain

Abstract: Hotspot chains, such as Louisville or Hawaii, are created by the interaction between an upwelling mantle plume and the lithosphere drifting over the plume (Wilson, 1963). The interaction creates a volcanic chain composed of tens of volcanoes and a topographic swell. The ages of the volcanoes increase from the youngest extremity of the chain, often associated with active volcanism, to the oldest extremity, which would have been above the plume millions to tens of millions of years ago. The swell is a positive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Data from hotspots not included in the above study, such as Amsterdam St Paul (∼6 Myr; Maia et al 2011;Sibrant et al 2019) andIceland (∼8 Myr, Parnell-Turner et al 2014), also show evidence of similar periods of melt flux variability. Additionally, Adam et al, 2022 suggest that ∼5-10 Myr signals observed from estimates of magmatic and swell flux variations at the Louisville hotspot are likely caused by shallow phenomena, in particular to instabilities within tilted plume conduits.…”
Section: Plume Periodicity and Viscosity Ratiomentioning
confidence: 96%
“…Data from hotspots not included in the above study, such as Amsterdam St Paul (∼6 Myr; Maia et al 2011;Sibrant et al 2019) andIceland (∼8 Myr, Parnell-Turner et al 2014), also show evidence of similar periods of melt flux variability. Additionally, Adam et al, 2022 suggest that ∼5-10 Myr signals observed from estimates of magmatic and swell flux variations at the Louisville hotspot are likely caused by shallow phenomena, in particular to instabilities within tilted plume conduits.…”
Section: Plume Periodicity and Viscosity Ratiomentioning
confidence: 96%